PELATIHAN DIGITAL MARKETING : MEWUJUDKAN MASYARAKAT INDUSTRI YANG MAMPU MEMANFAATKAN DIGITAL SEBAGAI NEW LANDS MARKET DALAM MEMPERLUAS PEMASARAN GITAR DESA MANCASAN - Siti Maryam; Shindy Tariska; Elshafira Dinia Yusufa; Dian Ratnasari; Dea Fitriana R (Universitas Islam Batik Surakarta, 2023)
Real work lectures conducted by students of the surakarta batik islamic university as a form of community service in mancasan village, baki sukoharjo sub-district, this real work lecture will start on october 3, 2022 until november 3, 2022. One of the kkn work programs this time is the development of smes through marketplace and the target is rw 12 rt 03 because that area is the center of mancasan guitar craftsmen. Before this socialization event was held, the kkn students made observations first in the rt12 area on guitar entrepreneurs who became the central point of balance. Implementation of community service program is carried out in a balanced manner with planning, implementation, and evaluation at the end of the program. The results that have been achieved with the socialization of msme development through this marletplace are the addition of insights on how to market a product through the marketplace, such as how to marketing a business, how to send products, how to withdraw through the marketplace app. With this socialization, it grows the interest and knowledge of entrepreneurs to market their products through the marketplace.